2001
DOI: 10.1046/j.1365-2249.2001.01528.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional heterogeneity of anti-endothelial cell antibodies

Abstract: SUMMARYWhile it has been claimed that some anti-endothelial cell antibodies (AECA) activate EC, there is also evidence that others trigger apoptosis. To address the issue of whether activation is a prerequisite for AECA-mediated apoptosis of EC, 23 AECA-positive sera were evaluated for their ability to induce activation and/or apoptosis. Activation was defined as an over-expression of E-selectin and intercellular adhesion molecule 1. Optical microscopy, annexin V binding, hypoploid cell enumeration, and determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 43 publications
0
32
0
1
Order By: Relevance
“…35 Alternatively, overall reduction of AECAs, as shown by suppressed immunoreactive luminal rat IgG in the ESb group, could have reduced local activation or apoptosis of endothelial cells 36,37 and prevented strokes. 38 E-selectin tolerization may also have suppressed local activity of a functional T-cell subset associated with ischemia in unstable angina, the IFN-␥-secreting CD4 ϩ CD28 null NK-T cells. 39 Although the precise molecular mechanisms for the strong stroke prevention conferred by mucosal tolerization to E-selectin remain to be clarified, the overall effect of this intervention is to target immunosuppression to activated vessel segments.…”
Section: Endothelial Cells That Have Been Activated By Ifn-␥ (Perhapsmentioning
confidence: 99%
“…35 Alternatively, overall reduction of AECAs, as shown by suppressed immunoreactive luminal rat IgG in the ESb group, could have reduced local activation or apoptosis of endothelial cells 36,37 and prevented strokes. 38 E-selectin tolerization may also have suppressed local activity of a functional T-cell subset associated with ischemia in unstable angina, the IFN-␥-secreting CD4 ϩ CD28 null NK-T cells. 39 Although the precise molecular mechanisms for the strong stroke prevention conferred by mucosal tolerization to E-selectin remain to be clarified, the overall effect of this intervention is to target immunosuppression to activated vessel segments.…”
Section: Endothelial Cells That Have Been Activated By Ifn-␥ (Perhapsmentioning
confidence: 99%
“…In vasculitides, it was suggested that endothelium was not only the target of injury, but also an active participant of vasculitic damage [9]. Anti-endothelial cell antibodies (AECA) have been described in various autoimmune and vasculitic disorders [10][11][12][13][14][15][16][17][18]. They have been implicated in the pathogenesis of vascular injury common to these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The cell ELISA for AECAs has been described previously (3,4,26,27). Briefly, EA.hy926 cells were fixed with 1% glutaraldehyde for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…A recent experimental model of systemic vasculitis has, based on auto-Ab idiotype, provided compelling evidence suggesting that some AECAs are pathogenic (5). Current efforts have focused on the EC activation of type II, which would be elicited by this or another group of AECAs (4). Evidence for such an activation includes upregulation of adhesion molecules, e.g., E-selectin and intercellular adhesion molecule 1 (ICAM-1).…”
mentioning
confidence: 99%